STUDENT LOYALTY IN PERSPECTIVE OF EDUCATION SERVICE QUALITY, CREATIVE PROMOTION AND STUDENT SATISFACTION - Nike Norma Epriliyana; Yusita Titi Hapsari; Andri Mardi Susanto (Jurnal Ilmu Manajemen Advantage, 2021)
Abstract This research aims to explain the student loyalty level through the perspective of education service quality, creative promotion, commitment, decision, and their satisfaction at private universities in Jember. We designed this research with a quantitative approach; it called explanatory research by a causal type. There are six research variables consisting of 3 (three) independent variables, 1 (one) intervening variable and 2 (two) dependent variables. The independent variables consist of the quality of education services (X1), creative promotion (X2), and commitment (X3). The dependent variable consists of satisfaction (Y1) and loyalty (Y2). The intervening variable consists of Decision (Z). The data collection technique carried out by distributing questionnaires online to 300 students of private universities in Jember. Data analysis carried out by using the Structural Equation Modeling (SEM) with AMOS (Analysis of Moment Structures) software. The research result showed that (1) the education service quality had no significant effect on students’ decision that indicated with a probability value: 0.058. (2) The education service quality had a significant effect on students’ satisfaction that indicated with the probability value: 0.000. (3) The creative promotion had a significant effect on students’ decision that indicated with the probability value: 0.000. (4) The student commitment had not significant effect on students’ decision that indicated with a probability value: 0.0760. (5) The student commitment had a significant effect on students’ loyalty that indicated with the probability value: 0.000. (6) The student decision had not significant effect on students’ satisfaction that indicated with a probability value: 0.611. (7) The student satisfaction had a significant effect on students’ loyalty that indicated with the probability value: 0.000. Keyword: education service quality, creative promotion, satisfaction, loyalty